Evolution and Function of Thioester-Containing Proteins and the Complement System in the Innate Immune Response - Shokal, Upasana; Eleftherianos, Ioannis (Frontiers in Immunology, 2017)
The innate immune response is evolutionary conserved among organisms. The complement system forms an important and efficient immune defense mechanism. It consists of plasma proteins that participate in microbial detection, which ultimately results in the production of various molecules with antimicrobial activity. Thioester-containing proteins (TEPs) are a superfamily of secreted effector proteins. In vertebrates, certain TEPs act in the innate immune response by promoting recruitment of immune cells, phagocytosis, and direct lysis of microbial invaders. Insects are excellent models for dissecting the molecular basis of innate immune recognition and response to a wide range of microbial infections. Impressive progress in recent years has generated crucial information on the role of TEPs in the antibacterial and anti-parasite response of the tractable model insect Drosophila melanogaster and the mosquito malaria vector Anopheles gambiae. This knowledge is critical for better understanding the evolution of TEPs and their involvement in the regulation of the host innate immune system.